Identification of effective fungicides for the management of false smut disease of rice - Ladhalakshmi, D; Prasad, M Srinivas; Laha, Gouri Shankar; Singh, Ram; Prakasam, V; Lore, Jagjeet Singh; Krishnaveni, D; Kannan, C (Indian Journal of Plant Protection, 2023)
Rice false smut pathogen Ustilaginoidea virens (teleomorph: Villosiclava virens) replaces the grain into powder form and causes direct economic yield loss. High intensity of the disease was reported from almost all the rice-growing regions of India during the favorable years with conducive climate conditions like drizzling or cooler climate during the booting to flowering stage. With scanty knowledge on host plant resistance, the disease has to be managed with available fungicides to prevent economic yield loss. Field trials were formulated and evaluated the efficacy of nine fungicides through the All India coordinated Rice Improvement Programme at two false smut hot spot locations, viz. CCSHAU Rice Research Station, Kaul, and Punjab Agricultural University, Ludhiana for two successive years (2016 and 2017). Each fungicide was sprayed once at the booting stage, followed by another application at ten days. Among the tested fungicides, azoxystrobin 18.2% + difenoconazole 11.4% w/w SC @ 1.0 ml/l and propiconazole (0.1%) significantly increased the grain yield by reducing the false smut disease severity at tested locations.